A Terrestrial Single Chamber Microbial Fuel Cell-based Biosensor for Biochemical Oxygen Demand of Synthetic Rice Washed Wastewater - Washington Logroño; Alex Guambo; Mario Pérez; Abudukeremu Kadier; Celso Recalde (Sensors, 2016)
Microbial fuel cells represent an innovative technology which allow simultaneous waste treatment, electricity production, and environmental monitoring. This study provides a preliminary investigation of the use of terrestrial Single chamber Microbial Fuel Cells (SMFCs) as biosensors. Three cells were created using Andean soil, each one for monitoring a BOD concentration of synthetic washed rice wastewater (SRWW) of 10, 100, and 200 mg/L for SMFC1, SMFC2 and SMFC3, respectively. The results showed transient, exponential, and steady stages in the SMFCs. The maximum open circuit voltage (OCV) peaks were reached during the elapsed time of the transient stages, according to the tested BOD concentrations. A good linearity between OCV and time was observed in the increasing stage. The average OCV in this stage increased independently of the tested concentrations. SMFC1 required less time than SMFC2 to reach the steady stage, suggesting the BOD concentration is an influencing factor in SMFCs, and SMFC3 did not reach it. The OCV ratios were between 40.6–58.8 mV and 18.2–32.9 mV for SMFC1 and SMFC2. The reproducibility of the SMFCs was observed in four and three cycles for SMFC1 and SMFC2, respectively. The presented SMFCs had a good response and reproducibility as biosensor devices, and could be an alternative for environmental monitoring.